The smart adolescent reproductive health promotion strategy based on android - Muthmainnah, Pulung Siswantara, Riris Diana R, (Opción, 2019)
The study was carried out aimed at developing adolescent reproductive health promotion based on Android via analysis research with Quasi-Experimental design. The results showed that there were significant differences between adolescent reproductive health knowledge before and after getting health promotion through an android application (p = 0.001 <0.05). In conclusion, adolescent reproductive health programs should be based on the needs, characteristics, and capacity of adolescents. Android application is a health promotion method that can be developed to increase knowledge and also can be used for baseline data on adolescent health.